Voice Quality Variation and the Perception of Affect: Continuous or Categorical? - NI CHASAIDE, AILBHE; GOBL, CHRISTER (My University, 2003)
This paper explores the mapping of voice quality to affect, for a synthesised tense ? lax voice continuum. Two questions are of interest. Firstly, over such a continuum, do listeners? attributions of affect change in a continuous or in a more categorical way? Secondly, might discreetly different affects emerge at different points in the continuum: specifically, might a moderately tense voice cue happy? Note that extremely tense does not appear to, but seems rather to be associated with the affect angry. A continuum of stimuli were synthesised ranging from a very tense quality at one end to a very lax quality at the other. Listeners rated their affective colouring in terms of the pairs of affective attributes: stressed/relaxed, angry/content, happy/sad, interested/bored, formal/intimate, and indignant/ apologetic. Results suggest that, for these voice qualities, listeners? attribution of affect is essentially continuous. Furthermore, moderate tension does not evoke happy.
Proceedings of the 15th International Congress of Phonetic Sciences
PUBLISHED
Barcelona
Keywords: Computer Science